Flipping-up the field: gravitational feedback as a mechanism for young clusters dispersal. Issue 3 (22nd July 2019) - Zamora-Avilés, Manuel; Ballesteros-Paredes, Javier; Hernández, Jesús; Román-Zúñiga, Carlos; Lora, Verónica; Kounkel, Marina
Abstract: Recent analyses of Gaia data have provided direct evidence that most young stellar clusters are in a state of expansion, with velocities of the order of ∼0.5 km s −1 . Traditionally, expanding young clusters have been pictured as entities that became unbound due to the lack of gravitational binding once the gas from the parental cloud that formed the cluster has been expelled by the stellar radiation of the massive stars in the cluster. In the present contribution, we used radiation-magnetohydrodynamic numerical simulations of molecular cloud formation and evolution to understand how stellar clusters form and disperse. We found that the ionizing feedback from the newborn massive stars expels the gas from the collapse centre, flipping-up the gravitational potential as a consequence of the mass removal from the inside–out. Since neither the parental clouds, nor the formed shells are distributed symmetrically around the H ii region, net forces pulling out the stars are present, accelerating them towards the edges of the cavity. We call this mechanism 'gravitational feedback', in which the gravity from the expelled gas appears to be the crucial mechanism producing unbound clusters that expand away from their formation centre in an accelerated way in young stellar clusters. This mechanism naturally explains the 'Hubble flow-like' expansion observed in several young clusters.